Pengembangan Media Pembelajaran Toys Painting by Number Bermuatan Budaya Lokal Malang sebagai Upaya Stimulasi Motorik Halus Anak Usia Dini TK Laboratorium UM - Joevanka, Vania Callista; Iriaji, Iriaji (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The development of local culture-based learning media is one of the strategic efforts to support early childhood development. This study aims to analyze the conditions and needs, develop and test the Toys Painting by Number learning media containing local Malang culture as an effort to stimulate fine motor skills of early childhood in the Laboratory Kindergarten, State University of Malang. The study used the ADDIE development method (Analysis, Design, Development, Implementation, Evaluation). Data collection techniques include observation, interviews, and expert validation questionnaires. Data analysis techniques consist of quantitative and qualitative descriptive analysis. The results of validation by material experts showed a feasibility level of 83%, while media expert validation reached 92%, both of which were in the very feasible category. The practicality test showed a positive response from students with an average score of 85%, which indicates that this media is interesting, easy to use, and practical in training fine motor skills and introducing local culture. This learning media is expected to be an innovative reference in the development of integrative and culture-based early childhood education.